About structure of curriculum for competence model of higher education - N. V. Sosnin (Moscow Polytechnic University, 2022)
The article considers the problems of reforming the structure of educational content in accordance with the competence model of higher education. The contradictions of transitionfrom traditional model to competence-based model are analyzed.